Is Dialetheism Where God of Religion and God of Philosophers Meet? More Questions than Answers - Rybarkiewicz, Dorota (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
The article is devoted to the question if paradoxes concerning actions and attributes of God can be solved in dialetheists’ manner. For the adherents of dialetheism theological texts where the contradictory nature of God is shown constitute the proof of their main thesis. Moreover, in one version of dialetheism the paradoxes imply that the very reality of God is inconsistent. This gives rise to the question if the classical criteria of truth apply to God. If one undermines the law of non-contradiction, the possibility to justify one’s stance is seriously reduced. In fact there are other possible causes of contradiction: equivocation, catachresis, crossing the limits of thought. As it seems, the most rational approach to inconsistency appearing in the description of God is to presume the logic that does not generate contradiction.